2020
DOI: 10.1029/2019gc008658
|View full text |Cite
|
Sign up to set email alerts
|

Seismic Anisotropy in the Java‐Banda and Philippine Subduction Zones and its Implications for the Mantle Flow System Beneath the Sunda Plate

Abstract: The Sunda Plate is a minor tectonic plate bounded by tectonically active convergent boundaries, below which are subducting: the Philippine Sea Plate to the east and the Indo-Australian Plate to the south and west. It is thus an ideal tectonic setting for investigating the interaction between subduction and asthenospheric flow. To better understand mantle interactions within the two nearly perpendicular subduction zones, we characterize seismic anisotropy by conducting a source-side sS splitting analysis, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(36 citation statements)
references
References 105 publications
(179 reference statements)
5
31
0
Order By: Relevance
“…Several seismic anisotropy investigations have been conducted in the central Sunda Plate and surrounding areas to explore the upper mantle seismic anisotropy and associated mantle deformation (Figure S1; Collings et al., 2013; Di Leo et al., 2012; Hammond et al., 2010; Kong, Gao, Liu, Zhang, et al., 2020; Wang & He, 2020; Xue et al., 2013; Y. Yu et al., 2018). While some SWS studies using local S and XKS (including SKS, SKKS, and PKS) waves suggested that the mantle wedge of the Sumatra subduction zone is generally isotropic (Hammond et al., 2010), trench‐orthogonal azimuthal anisotropy has been observed and attributed to a corner flow system in the mantle wedge using data recorded by two temporary seismic networks (Collings et al., 2013).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several seismic anisotropy investigations have been conducted in the central Sunda Plate and surrounding areas to explore the upper mantle seismic anisotropy and associated mantle deformation (Figure S1; Collings et al., 2013; Di Leo et al., 2012; Hammond et al., 2010; Kong, Gao, Liu, Zhang, et al., 2020; Wang & He, 2020; Xue et al., 2013; Y. Yu et al., 2018). While some SWS studies using local S and XKS (including SKS, SKKS, and PKS) waves suggested that the mantle wedge of the Sumatra subduction zone is generally isotropic (Hammond et al., 2010), trench‐orthogonal azimuthal anisotropy has been observed and attributed to a corner flow system in the mantle wedge using data recorded by two temporary seismic networks (Collings et al., 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Mantle flow dominantly driven by the rollback of the subducted Indian slab was proposed to interpret the pervasively E‐W fast orientations beneath the Indochina Peninsula (Y. Yu et al., 2018). A source‐side sS splitting analysis recently revealed the existence of simple 2‐D corner flow in the Java and Philippine subduction zones (Wang & He, 2020). Thus, the spatial variation of mantle anisotropy and inferred mantle deformation beneath the central Sunda plate are still poorly constrained.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, to better understand the deformation characteristics in the complex tectonic region, we show upper mantle anisotropic fabrics constrained by measuring teleseismic SKS-wave splitting from new seismic data collected from seven broadband stations, six of which have been deployed for long-term observation (>12 years). Also, previous shear-wave splitting measurements (Di Leo et al, 2012aLeo et al, , 2012bRoy et al, 2017;L. Wang & He, 2020) and a Vp velocity model UU-P07 by Amaru (2007) are combined to shed light on the regional upper mantle flow patterns at the corner between the Pacific and Tethys domains.…”
mentioning
confidence: 99%